2019
DOI: 10.1002/bit.27094
|View full text |Cite
|
Sign up to set email alerts
|

Using kinetics and modeling to predict denitrification fluxes in elemental‐sulfur‐based biofilms

Abstract: Elemental sulfur (S 0 ) can serve as an electron donor for water and wastewater denitrification, but few researchers have addressed the kinetics of S 0 -based reduction of nitrate (NO 3 − ), nitrite (NO 2 − ), and nitrous oxide (N 2 O). In addition, S 0based denitrifying biofilms are counter-diffusional. This is because the electron donor (S 0 ) is supplied from the biofilm attachment surface while the acceptor, for example, NO 3 − , is supplied from the bulk liquid. No existing mathematical model for S 0 -bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Biofilm growth/decay in the short and long term, and the impact of the biofilm thickness on denitrification efficiency and current demand should also be kept in consideration as substrate diffusion in the biofilm may greatly affect the denitrification process. 50,51 Perchlorate is often concomitant with NO 3 − in groundwater, has a similar reduction potential (0.75 for NO 3 − /N 2 and 0.87 for ClO 4 − /Cl), and may compete for electrons in biocathodic denitrification: 52 the presence of an additional TEA may strongly influence the denitrification kinetics also due to the different optimal pH for reduction Environmental Science: Water Research & Technology Paper overall denitrification process; similar findings were reported by Clauwaert et al 53 for denitrifying biocathodes in MFCs.…”
Section: Limits Of the Model And Perspectivesmentioning
confidence: 99%
“…Biofilm growth/decay in the short and long term, and the impact of the biofilm thickness on denitrification efficiency and current demand should also be kept in consideration as substrate diffusion in the biofilm may greatly affect the denitrification process. 50,51 Perchlorate is often concomitant with NO 3 − in groundwater, has a similar reduction potential (0.75 for NO 3 − /N 2 and 0.87 for ClO 4 − /Cl), and may compete for electrons in biocathodic denitrification: 52 the presence of an additional TEA may strongly influence the denitrification kinetics also due to the different optimal pH for reduction Environmental Science: Water Research & Technology Paper overall denitrification process; similar findings were reported by Clauwaert et al 53 for denitrifying biocathodes in MFCs.…”
Section: Limits Of the Model And Perspectivesmentioning
confidence: 99%
“…The nucleophilic attack between sulfide (S 2− ) and S 0 under neutral or alkaline conditions results in the cleavage of S 8 0 rings and the formation of polysulfide (S n 2− ) as detailed in Equation ( 2) [20]. This chemical reaction has received much attention due to the higher solubility and bioavailability of S n 2− [20,28,29]. Therefore, the polysulfide-involved SADN (PiSADN) process (Equation (3)) might be an effective method for realizing high-rate NO 3 − removal.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, mathematical modelling is a useful tool to elucidate the competition among different microbial families and the performances in terms of nitrate removal and sulfate production occurring during the SdAD process. Indeed, previous mathematical models with elemental sulfur as electron donor have been mainly focused on evaluating the kinetics of the process in terms of nitrate removal 20 22 , nitrite accumulation 5 and N 2 O emission 23 , 24 . In addition, the co-occurrence of SdAD and heterotrophic denitrification 17 , 25 has been also modelled to investigate the same parameters.…”
Section: Introductionmentioning
confidence: 99%